How good are manufacturing jobs in Myanmar? Evidence from matched employer-employee data - Paolo Falco; Francesca Gioia; Neda Trifkovic (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2021)
The quality of people's jobs is a fundamental determinant of their well-being, and judging the state of a labour market on the basis of job quantity alone delivers a very partial picture. This study is an attempt to place the spotlight on the working conditions of workers in the Myanmar manufacturing sector. Using a model of job demands and job resources, we focus on the balance between different stress factors and the support workers get. We find that a large fraction of workers face severe pressures. In particular, nearly one half faces severe time pressure; nearly a quarter is exposed to health hazards, such as loud noises, carrying heavy loads, and operating in uncomfortable or painful positions. These factors are often not met with adequate support from the firm. Male workers and those with lower levels of education are most exposed to occupational risks. Contrary to the narrative that a trade-off might exist between firm competitiveness and job quality, we find that labour productivity is higher in firms where working conditions are better.
Keywords: D22; J81; L2; P2; O53; 330; job quality; productivity; working conditions; Myanmar